2009
DOI: 10.1111/j.1365-2265.2008.03441.x
|View full text |Cite
|
Sign up to set email alerts
|

Octreotide LAR vs. surgery in newly diagnosed patients with acromegaly: a randomized, open‐label, multicentre study

Abstract: This first randomized study in unselected patients indicates that the 48-week treatment outcome of octreotide LAR as first-line treatment of acromegaly does not significantly differ from surgery. As a complete response to surgery in GH-secreting macro-adenomas can be difficult, first-line therapy with octreotide LAR can be considered as a viable alternative for most patients with acromegaly, due to its low complication rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
60
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(67 citation statements)
references
References 40 publications
7
60
0
Order By: Relevance
“…A significant proportion of patients with large macroadenomas extending outside the sella will experience persistently elevated GH levels postoperatively, often requiring subsequent medical therapy and/or radiosurgery to gain satisfactory biochemical control. 5,18 Some authors have argued primary medical therapy may be used for patients with GH-secreting macroadenomas with extrasellar extension, which makes complete surgical resection unfeasible. 5,18 However, other authors have asserted that initial operative debulking of these macroadenomas may increase the proportion of patients that subsequently attain hormonal control with adjunctive therapy, particularly if more than 75% of the initial tumor volume is resected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A significant proportion of patients with large macroadenomas extending outside the sella will experience persistently elevated GH levels postoperatively, often requiring subsequent medical therapy and/or radiosurgery to gain satisfactory biochemical control. 5,18 Some authors have argued primary medical therapy may be used for patients with GH-secreting macroadenomas with extrasellar extension, which makes complete surgical resection unfeasible. 5,18 However, other authors have asserted that initial operative debulking of these macroadenomas may increase the proportion of patients that subsequently attain hormonal control with adjunctive therapy, particularly if more than 75% of the initial tumor volume is resected.…”
Section: Discussionmentioning
confidence: 99%
“…5,18 Some authors have argued primary medical therapy may be used for patients with GH-secreting macroadenomas with extrasellar extension, which makes complete surgical resection unfeasible. 5,18 However, other authors have asserted that initial operative debulking of these macroadenomas may increase the proportion of patients that subsequently attain hormonal control with adjunctive therapy, particularly if more than 75% of the initial tumor volume is resected. 17,35,48,54 To demonstrate safety and efficacy an attempt was made to carefully evaluate and report the biochemical results of endoscopic resection of GH-secreting adenomas in the current series.…”
Section: Discussionmentioning
confidence: 99%
“…In the prospective multicenter studies with both octreotide LAR and lanreotide autogel, biochemical control of acromegaly was obtained in about 30 % of the patients, and tumor shrinkage was observed in *75 % of the patients [10,11]. SSAs have also been compared with surgery as the primary treatment for acromegaly in a randomized-controlled trial including 101 patients; this trial showed that the two interventions do not differ in terms of biochemical and tumor control outcomes [14]. In all of these prospective trials with SSA, the drugs showed good safety profiles with no serious adverse events.…”
Section: Cabergoline As a Monotherapymentioning
confidence: 99%
“…Somatostatin analogues are considered the first option of medical treatment in the majority of patients, but prospective randomized studies show control rates of 20-40% for patients with first-generation SA (4,(7)(8)(9)(10)(11). Pasireotide LAR, a next-generation SA (not yet approved for acromegaly treatment in Brazil), allows disease control in a higher percentage of patients and is effective in approximately 15% of those patients not controlled by first-generation SA with the dose of 40 mg and in 20% of the patients with the dose of 60 mg (12,13).…”
Section: Introductionmentioning
confidence: 99%